2016
DOI: 10.1021/acs.biochem.6b00748
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Analyses of Interaction between a High-Affinity RNA Aptamer and Its Target Protein

Abstract: AML1 (RUNX1) protein is an essential transcription factor involved in the development of hematopoietic cells. Several genetic aberrations that disrupt the function of AML1 have been frequently observed in human leukemia. AML1 contains a DNA-binding domain known as the Runt domain (RD), which recognizes the RD-binding double-stranded DNA element of target genes. In this study, we identified high-affinity RNA aptamers that bind to RD by systematic evolution of ligands by exponential enrichment. The binding assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 62 publications
0
46
0
1
Order By: Relevance
“…HTS data were compared with the sequences of the 36 clones in the 8R RNA pool that were determined using the capillary sequencing method 45 . The fractions of each aptamer were determined as follows: S1, 27.8%; S2, 22.2%; S3, 16.7%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…HTS data were compared with the sequences of the 36 clones in the 8R RNA pool that were determined using the capillary sequencing method 45 . The fractions of each aptamer were determined as follows: S1, 27.8%; S2, 22.2%; S3, 16.7%.…”
Section: Resultsmentioning
confidence: 99%
“…We focused on the aptamers S1 and S2, which were sufficiently abundant to observe them in the pool, although other aptamers that showed higher affinity to RD than these two aptamers were obtained in a previous study 45 . Given that HTS data revealed that the fraction of S1 and S2 was high at 5–8R, we prepared isolated S1 and S2 aptamers and compared the imino proton spectra of 5–8R RNA pools with those of S1 and S2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations